THE EFFECT OF SUB-CLINICAL INFECTION WITH HARMONCHUS CONTORTUS ON BODY WEIGHT OF LAMBS AND MILK PRODUCTION IN EWES - A. Ali, D.; M. Al-Saqur‎, I.; T. Jirjees‎, M. (The Iraqi Journal of Veterinary Medicine, 2024)
The effect of sub-clinical level of H. contortus infection (500 larvae/kg. bodyweight) over the lambing period and first 6 weeks of lactation on lambs birth weight, milk yield and composition were noted. This level of infection was significantly reflected (5%) on lamb birth weight, while lamb weight gain was not markedly affected. During lactation, infected ewes produced 14% less milk and this was highly significant at 1% level, despite the associated fall in egg count. Infected ewes showed a significant reduction (5%) in the milk protein percentage, while milk fat percentage was not substantially affected. Thus the ewe appears to be particularly susceptible to the effect of parasitism at this time.